Pointwise Inequalities of Landau–Kolmogorov Type for Functions Defined on a Finite Segment - Babenko, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For arbitrary t ∈ [0, 1], s ∈ [1, ∞], and A ≥ 2, we determine the unimprovable constant B for the inequality | x′ ( t ) | A\| x \|_L_∞ [ 0,1 ] + B\| x \|_L_s [ 0,1 ] . .